Urgensi Bimbingan Konseling Islam dalam Tantangan Karakteristik Generasi Z - Khoirina Nur Salamah (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
Humans are creatures created perfectly by Allah SWT compared to other creatures because they have the special ability of reason to think, which can be used to distinguish between what is right and what is wrong so that they can live life more carefully and as best as possible. Certainly, possessing reason is not meant for humans to always feel capable of understanding themselves or even selfishly live life just for themselves, so humans as social creatures are required to help each other in goodness, such as in the context of self-improvement. Helping each other in goodness has been regulated by Islam as an important counseling guidance process for the life of the technologically advanced generation today. The technology generation or internet generation, commonly referred to as Generation Z, has prominent characteristics that can have both positive and negative values, making guidance in the aspect of spirituality very necessary, which in this context is in Islamic counseling guidance. This research needs to be carried out to reveal the urgency of Islamic counseling guidance in facing the characteristic challenges of Generation Z, and it was found that the characteristics of Generation Z are very important to be directed through the principles of Islamic counseling guidance because they align with the needs of Generation Z as the next generation of the nation, thus achieving the human goal of obtaining happiness in this world and the hereafter.